2003
DOI: 10.2136/sssaj2003.1220a
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and Desorption of Pesticides by Clay Minerals and Humic Acid‐Clay Complexes

Abstract: In soils, organic matter and minerals are often associated such that it is unclear how the presence of the former component influences the sorptive properties of the latter one. In this study, sorption and desorption of the herbicides 4,6‐dinitro‐o‐cresol (C7H6N2O5) and dichlobenil (C7H3Cl2N) by Ca2+–, K+–smectites, and humic acid–smectite complexes, was investigated using batch‐equilibrations and x‐ray diffraction (XRD). Greater sorption of 4,6‐dinitro‐o‐cresol compared with dichlobenil was observed for both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The measured basal spacings of the air-dried and rewetted K-SWy-2 clay films were plotted against their corresponding concentrations of adsorbed NACs (Figure 5). The data for 4,6-dinitro-o-cresol were adapted from a previous study (26) for comparison. Basal spacings of air-dried films increased progressively from 10.2 to 12.2 Å as the sorbed NAC concentrations increased, demonstrating the intercalation of NACs into the smectite interlayers.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
“…The measured basal spacings of the air-dried and rewetted K-SWy-2 clay films were plotted against their corresponding concentrations of adsorbed NACs (Figure 5). The data for 4,6-dinitro-o-cresol were adapted from a previous study (26) for comparison. Basal spacings of air-dried films increased progressively from 10.2 to 12.2 Å as the sorbed NAC concentrations increased, demonstrating the intercalation of NACs into the smectite interlayers.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
“…[11][12][13] In prior sorption studies, the nature of the exchangeable cation was shown to significantly influence the uptake of aromatic hydrocarbons as well as semi-polar, planar aromatic compounds including nitroaromatics, triazines and carbamates. 11,12,[14][15][16][17][18][19][20][21][22][23][24][25][26] Sorption of these compounds possessing moderately polar functional groups on smectites from aqueous was influenced by several key parameters. First, the interaction between the compound and exchangeable cation influences sorption.…”
Section: Introductionmentioning
confidence: 99%
“…Since no herbicide affected the quality of harvested biomass (assessed using Brix), the main evaluated variable that correlates with productivity is BMP. In this case, of the 16 treatments evaluated in this type of soil, nine did not affect this variable and can be considered selective for sweet sorghum: atrazine (2000, 1500 and 1000 g ha -1 ), amicarbazone (280 g ha -1 ), S-metolachlor (480 g ha -1 ), pendimethalin Generally, organic matter and clay minerals are the main factors in the retention of herbicides applied to the soil (Li et al, 2003).…”
Section: Clay Soilmentioning
confidence: 90%